2011
DOI: 10.4103/2230-8210.81938
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy and safety of orlistat in obese patients

Abstract: Context:Rapidly rising prevalence of obesity is alarming. Obesity predisposes to co-morbidities like hypertension, type 2 diabetes mellitus, dyslipidemias, thus substantially rising healthcare expenditure. Lifestyle modifications alone have very limited success, necessitating the addition of pharmacotherapy to it.Objective:Present study was carried out to evaluate the efficacy and safety of orlistat in obese patients.Materials and Methods:Eighty obese (BMI>30) patients according to inclusion and exclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…Orlistat therapy in the current study produced a significant reduction in BMI, TC, WC without significant effects on VAI compared to baseline values. These findings corresponded with other studies which demonstrated that orlistat therapy produced a significant body weight reductions in obese patients with additional amelioration on lipid profile, anthropometric measures, inflammatory markers (tumor necrosis factor a [TNF-a] and interleukin 6 [IL-6]), and cardiometabolic risk factors [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Orlistat therapy in the current study produced a significant reduction in BMI, TC, WC without significant effects on VAI compared to baseline values. These findings corresponded with other studies which demonstrated that orlistat therapy produced a significant body weight reductions in obese patients with additional amelioration on lipid profile, anthropometric measures, inflammatory markers (tumor necrosis factor a [TNF-a] and interleukin 6 [IL-6]), and cardiometabolic risk factors [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that betulinic acid may inhibit the uptake of dietary fat. Although the inhibitory activity of orlistat was stronger than that of betulinic acid, orlistat causes serious gastrointestinal side effects such as oily stools, abdominal pain and fecal urgency (Jain et al ., ). Botanicals may provide safe, natural and cost‐effective alternatives to synthetic drugs (Zdunczyk et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…A range of strategies can be employed for weight loss which includes lifestyle changes (diet, exercise), behavioral therapy, pharmacotherapy, and surgery. Orlistat is an effective and well-tolerated antiobesity drug, which can be employed as an adjunct to therapeutic lifestyle changes to achieve and maintain optimal weight [ 25 ]. But most antiobesity drugs act on the central nervous system to suppress appetite, reduce food intake, and have serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%